2019
DOI: 10.1126/science.aaw2493
|View full text |Cite
|
Sign up to set email alerts
|

Structures of human Na v 1.7 channel in complex with auxiliary subunits and animal toxins

Abstract: Voltage-gated sodium channel Nav1.7 represents a promising target for pain relief. Here we report the cryo–electron microscopy structures of the human Nav1.7-β1-β2 complex bound to two combinations of pore blockers and gating modifier toxins (GMTs), tetrodotoxin with protoxin-II and saxitoxin with huwentoxin-IV, both determined at overall resolutions of 3.2 angstroms. The two structures are nearly identical except for minor shifts of voltage-sensing domain II (VSDII), whose S3-S4 linker accommodates the two GM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
509
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 383 publications
(566 citation statements)
references
References 67 publications
24
509
1
1
Order By: Relevance
“…Icilin/Ion channel TRPM8 (PDB:6NR3, EMD:0487) 41 ; LY2119620/M2R (PDB:6OIK, EMD:20079) 38 ; Iperoxo/M2R (PDB:6OIK, EMD:20079) 38 ; Saxitoxin/Nav1.7 (PDB: 6J8G, EMD:9781) 39 ; Biculine/GABAA (PDB:6HUK, EMD:0280) 37 ; Xanax/GABAA (PDB:6HUO, EMD:0282) 37 ; Valium, GABAA (PDB:6HUP, EMD:0283) 37 ; NDI-091143/ATP Citrate Lyase (PDB:6O0H, EMD:0567) 7 ; paroxetine/serotonin transporter (PDB:6DZW, EMD:8941) 40 ;…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Icilin/Ion channel TRPM8 (PDB:6NR3, EMD:0487) 41 ; LY2119620/M2R (PDB:6OIK, EMD:20079) 38 ; Iperoxo/M2R (PDB:6OIK, EMD:20079) 38 ; Saxitoxin/Nav1.7 (PDB: 6J8G, EMD:9781) 39 ; Biculine/GABAA (PDB:6HUK, EMD:0280) 37 ; Xanax/GABAA (PDB:6HUO, EMD:0282) 37 ; Valium, GABAA (PDB:6HUP, EMD:0283) 37 ; NDI-091143/ATP Citrate Lyase (PDB:6O0H, EMD:0567) 7 ; paroxetine/serotonin transporter (PDB:6DZW, EMD:8941) 40 ;…”
Section: Methodsmentioning
confidence: 99%
“…Using GlideEM we were able to identify candidate poses in this resolution range with cross correlations that were comparable to the deposited poses for all of the structures that we studied. For GABAA in complex with three different ligands 37 , the M2 muscarinic acetylcholine receptor in complex with two different ligands 38 , the sodium channel Nav1.7 with one ligand 39 , ATP citrate lyase with one ligand 7 , and the serotonin transporter with two different ligands 40 the poses we identified with GlideEM largely agreed with what was deposited in the PDB ( Supplementary Fig. 7) (although it should be noted that for the deposited structures of the M2 receptor and serotonin transporter the ligands were docked with the traditional version of Glide).…”
Section: Using Gemspot With 30-45 å Resolution Mapsmentioning
confidence: 99%
“…Notably, the upper region of the selectivity filter near the KIIIA binding site has a minimum radius of ~2.5 Å, which is large enough to potentially allow sodium ion conduction and consistent with the characteristic incomplete block of Nav channels by KIIIA (13,15). Notably, KIIIA is positioned just above the selectivity filter which is different from small molecular toxins, such as TTX and STX, which are positioned deeper into the selectivity region (25,26).…”
Section: Molecular Modeling Reveals Asymmetric Binding Of Kiiia To Hnmentioning
confidence: 83%
“…Another feature of the molecular mechanism of KIIIA binding are differences in the reversibility and irreversibility of some of the KIIIA mutants on different Nav channels. Cryo-EM structures of hNav1.2, hNav1.4, and hNav1.7 channels (25,31,32) revealed that the extracellular vestibule of the channel pore targeted by KIIIA is surrounded by several relatively long loop regions raising the possibility that KIIIA access pathway to the toxin binding site is relatively narrow. Restricted access and escape pathways for KIIIA binding agree with the relatively slow kon and koff rates observed in previously published data (2,13,15) and our functional studies (Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…Structural models of human SCN5A (UniProtKB accession number: Q14524-1, modeled residues: 30-440, 685-957, 1174-1887) bound with SCN1B (UniProtKB accession number: Q07699-1, modeled residues: 20-192) were generated by homology modeling using the protein structure prediction software Rosetta (version 3.10). 31 The cryo-EM structure of human SCN9A bound with SCN1B and the Ig domain of SCN2B resolved to 3.2 Å (PDB 6J8H) 32 was used as the primary template while the cryo-EM structure of NavPaS from American Cockroach resolved to 2.6 Å (PDB ID: 6A95) 33 Methods and Table S4.…”
Section: Homology Model and Structural Calculationsmentioning
confidence: 99%